The Reverse Oblique Supracondylar Humerus Fracture: Description of a Novel Fracture Pattern. Issue 2 (February 2020) - Heffernan, Michael J.; Lucak, Thomas; Igbokwe, Linus; Yan, Justin; Gargiulo, Dominic; Khadim, Muayad
Abstract : Background: Sagittal profile descriptions of supracondylar humerus fractures are limited. We describe a reverse oblique (RO) pattern in which the distal fragment has a prominent anterior spike that is displaced posterior to the proximal fragment. This pattern presents a challenge during closed manipulation utilizing traditional reduction maneuvers. The purpose of this study is to compare the clinical and radiographic characteristics of the RO and non-RO patterns of supracondylar humerus fractures. We hypothesized that the RO pattern would be associated with greater soft tissue trauma. Methods: Retrospective evaluation of operative supracondylar humerus fractures treated at a tertiary pediatric hospital from 2014 to 2016. Patients were categorized into RO and non-RO groups for analysis. Associated neurovascular injuries were compared between groups. Results: Two hundred ninety-nine consecutive patients were reviewed. The RO fracture pattern was seen in 12 patients. All displaced RO fractures were able to be closed reduced with a modification to the traditional reduction sequence. Overall cohort rates of preoperative soft tissue injury included antecubital ecchymosis 16.8%, nerve palsies 15%, and vascular compromise 6.4%. Compared with non-RO fractures, the RO fracture group had significantly higher rates of anterior interosseous nerve (AIN) palsies ( P =0.013), antecubital ecchymosis ( P =0.018), and compartment syndrome ( P =0.043). When comparing RO with non-RO type II fractures, there were no differences in soft tissue injury ( P =0.439). Compared with non-RO type III fractures, RO type III fractures had higher rates of AIN injury ( P =0.047), antecubital ecchymosis ( P =0.007), and overall soft tissue injury ( P =0.009). Conclusions: This study introduces a previously undescribed supracondylar humerus fracture subtype: the RO fracture. We found increased rates of soft tissue compromise including antecubital ecchymosis and AIN palsy in this fracture type. Further, traditional reduction methods proved to be ineffectual for this fracture pattern. We utilized a simple modification that allowed for closed reduction and percutaneous pinning of displaced RO fractures. Level of Evidence: Level III—prognostic.